Comparative codicological and structural analysis of two Italian Hebrew manuscripts - E.D. Zarubina (Ученые записки Казанского университета: Серия Гуманитарные науки)
The current paper is devoted to analysis of codicological and compositional characteristics of two manuscripts coming from Jewish communities of early modern Modena and Venice. Two aspects of the research define its novelty. Firstly, the understanding of Italian Jewish history is essential for analysis of socioeconomic processes that took place in the eastern Mediterranean of that time. Secondly, the documents under consideration represent an understudied complex of sources, namely fraternities' minute books. The paper has two major aims. First of them is to present collected data concerning the codicological peculiarities of the manuscripts. The second aim is to analyze the evolution of the pinkhas genre. The objectives of the research included examination of the codicological (paper, handwriting types etc.) and structural characteristics of the manuscripts. In the course of work, quantitative and codicological methods, as well as comparison with the historical context have been applied. Summarizing the results of the research, we have been able to conclude that the major structural components of the minute books are charter and dated notes. The manuscript from Venice represents the early form of the pinkhas genre, while the document from Modena belongs to the later stage. In the Modena pinkhas, the charter part is reduced and the narrative element in the dated notes is strengthened. The complex of the revealed peculiarities of the manuscripts is closely connected with the historical context of their creation. The results of the analysis are widely adaptable. Firstly, the alignment of the obtained codicological data is essential for the subsequent research of the manuscripts. Secondly, the analyzed information concerning the structure of the texts enables us to reconstruct the development of the pinkhas genre in Italy and relate it to the evolution of fraternities. Finally, the minute books make up a crucial set of sources concerning the Jewish history of the Mediterranean and studying their major compositional characteristics makes the choice of sources for any subsequent research more effective.